If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z(z + -3) + 2(z + 3) = 18 Reorder the terms: z(-3 + z) + 2(z + 3) = 18 (-3 * z + z * z) + 2(z + 3) = 18 (-3z + z2) + 2(z + 3) = 18 Reorder the terms: -3z + z2 + 2(3 + z) = 18 -3z + z2 + (3 * 2 + z * 2) = 18 -3z + z2 + (6 + 2z) = 18 Reorder the terms: 6 + -3z + 2z + z2 = 18 Combine like terms: -3z + 2z = -1z 6 + -1z + z2 = 18 Solving 6 + -1z + z2 = 18 Solving for variable 'z'. Reorder the terms: 6 + -18 + -1z + z2 = 18 + -18 Combine like terms: 6 + -18 = -12 -12 + -1z + z2 = 18 + -18 Combine like terms: 18 + -18 = 0 -12 + -1z + z2 = 0 Factor a trinomial. (-3 + -1z)(4 + -1z) = 0Subproblem 1
Set the factor '(-3 + -1z)' equal to zero and attempt to solve: Simplifying -3 + -1z = 0 Solving -3 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1z = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1z = 0 + 3 -1z = 0 + 3 Combine like terms: 0 + 3 = 3 -1z = 3 Divide each side by '-1'. z = -3 Simplifying z = -3Subproblem 2
Set the factor '(4 + -1z)' equal to zero and attempt to solve: Simplifying 4 + -1z = 0 Solving 4 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1z = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1z = 0 + -4 -1z = 0 + -4 Combine like terms: 0 + -4 = -4 -1z = -4 Divide each side by '-1'. z = 4 Simplifying z = 4Solution
z = {-3, 4}
| 5h+4=4h+11 | | w(20w-73)=-63 | | 6(x^2+x-20)=0 | | 5n+43=-2(1-7n) | | 6y-8=4y+2 | | 7+7x=7+8x | | x+5x+4x-6=180 | | 7=4y-2y+1 | | 3v-5=16 | | z^2-30z+c=0 | | (13b-7)-3(4b+3)=-6 | | 4x-5=(x-1) | | 3.5(x-2)=12-.5x | | -63+8x=173x | | 4x^3-80x^2+400x=500 | | -9x-155=85+3x | | 5x-3=-x+3 | | 10+3x=-5x+98 | | 5b+3=4b-2 | | 6x-4=-4-2x | | 3x+9=2y-4 | | 6m^2+15m+3=0 | | -2x+5=10+4x | | 2x+4=-x-20 | | 22=2y | | 0=x^2+26x+232 | | x+1+2x+2+3x+3+4x=56 | | 2x+7=-x-1 | | 11x-79=47+5x | | 5x-3+2x=2x+2 | | 8=2*b^2 | | (x*x)-5=23 |